Pengaruh Complex Training Terhadap Peningkatan Power Otot Tungkai Pada Atlet Bola Voli Putri - Ayu Safitri; Mochammad Yamin Saputra; Yopi Kusdinar; Fitri Rosdiana (Jurnal Keolahragaan, 2025)
In volleyball games that are applied and the most important thing is the jump compared to the hit that must be done quickly and strongly. One factor to get a fast and strong jump with Power training with the Complex Training training method. Therefore, this study aims to examine the effect of Complex Training on increasing muscle power abilities in female volleyball athletes. The research method in this study used an experiment with One-Group Pretest-Posttest Design. The sample involved in this study consisted of 12 female athletes of the UPI volleyball UKM, using the total sampling technique from all populations. The research instrument used was the Force Plate Test which was given twice, before and after treatment was given. A t-test was carried out with SPSS version 25 as a data analysis technique. Based on the results of the study, it showed that the Complex Training training method on muscle power fitness had a significant value (0.000) <0.05, with an increase in muscle power fitness abilities in female volleyball athletes of UKM at the Indonesian Education University. It is concluded that there is a significant effect of the Complex Training training method on the muscle strength of female volleyball athletes.Keywords: Leg muscle power, Complex Training, Leg muscle power in volleyball, volleyball game.